- 1-800-665-6601
- [email protected]

Expressions |
Number of terms used |
Terms |

7 x + 3 x y + 2 y | 3 | 7x, 3xy, 2y |

2 x + 5 x y | 2 | 2 x, 5 x y |

4 x – 6 y + 7 | 3 | 4 x, 6 y, 7 |

7 x y + 2 a / y – 3 z + 8 | 4 | 7 x y, 2 a / y, 3 z, 8 |

In algebraic expression 4 x – y + 7; 7 is the constant term as it does not contain any variable. Similarly in algebraic expression 7 x y + 2 a / y – 3 z + 8; 8 is the constant term.

x^3 +x^2 + x +1

x^3 +x^2 + x +1 = (- 1)^3 + (- 1)^2 + (- 1) + 1

= - 1 + 1 – 1 + 1

= -2 + 2

= 0

= (x + 1) (x^2 + 1)